Analysis of the Needs for Developing a Pocketbook on Eruption Disaster Mitigation Based on Local Vocabulary of the Mount Merapi Slope Community in Kabupaten Klaten - Anggraheny, Kunthum Ria; Sholihah, Umi (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
Communication is one component of disaster mitigation, conveying information related to disasters is necessary in reducing disaster risk. The use of foreign vocabulary for disaster terms is difficult to understand for the elderly on the slopes of Mount Merapi, so this research aims to determine the need for a disaster mitigation pocketbook based on local vocabulary in reducing disaster risks and identifying local vocabulary for the Merapi Eruption disaster in mountain slope communities. Developing of a disaster mitigation pocketbook using the ADDIE model is Analysis, Design, Development, Implementation, and Evaluation, research is only in the first stage of the 5 stages, limited to the analysis stage. Respondents in this study were elderly people and elderly companions, in three villages on the slopes of Mount Merapi, namely Sidorejo, Tegalmulyo, and Balerante villages, which are villages directly affected by the eruption of Mount Merapi. The results of the needs analysis showed that 88% of elderly companions agreed with the existence of a disaster mitigation pocketbook based on local vocabulary, while for the elderly 86% agreed. The incorrect local vocabulary identification is the term "lava flood" in the local vocabulary "bena lenduth". Developinh a disaster mitigation pocketbook based on local vocabulary is expected to provide informative communication between elderly companions and the elderly in increasing disaster preparedness.